Pengaruh Covid 19 Terhadap Tingkat Kesehatan Koperasi Simpan Pinjam - Sumiyati Sumiyati; Sulistia Suwondo; Yanti Rufaedah; Muhammad Jiddan Zamhar (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the health level of cooperatives, in Koperasi Keluarga Besar Dispenda Provinsi Jawa Barat (KKBD) for the 2019-2020 period when the covid 19 pandemic occurred, in terms of seven aspects of the assessment, namely, aspects of capital, quality of productive assets, management, liquidity, efficiency, independence and growth and identity of cooperatives. This research is a descriptive evaluative research, with primary and secondary data sources. The data analysis technique used is collected through interviews and financial statement documents such as: balance sheet, report on calculation of operating results (PHU) and report on remaining operating results (SHU). In relation to cooperative health, the savings and loan business health model is used which refers to Ministerial Regulation No.14/Per/M.KUKM/XII/2009. The results of this study indicate that the West Java Province KKBD in terms of the aspect of capital quality obtained a perfect score in 2019 and 2020 with a score of 12, so it is included in the category or predicate Healthy. For the aspect of earning asset quality, it obtained an average score from 2019 to 2020 with an average score of 16, so that the quality aspect of earning assets is under supervision. Judging from the quality of management obtained an average score of 13.6, so that the management aspect is categorized as healthy. Judging from the quality aspect of efficiency, it obtained an average score of 5, so it was categorized in special supervision. For the quality of liquidity obtained an average score of 5.625, so it is categorized under special supervision. For the aspect of independence and cooperative growth, it obtained an average score of 4.5, so it was categorized under special supervision. Meanwhile, the cooperative's identity quality has an average score of 4.375, so it is categorized under special supervision.